Load frequency control enhancement of islanded micro-grid considering high wind power penetration using superconducting magnetic energy storage and optimal controller. Issue 6 (December 2019) - Mohamed, Emad A; Mitani, Yasunori
This article proposes a robust load frequency control using a new optimal proportional–integral–derivative controller–based genetic moth swarm algorithm for islanded microgrids considering high wind power penetration. In such microgrids, the replacement of conventional generator units with a large number of renewable energy sources reduces the system inertia, which in turn causes undesirable influence on microgrid frequency stability, leading to weakening of the microgrid. Furthermore, sudden load shedding, load restoring, and short circuits caused large frequency fluctuations which threaten the system security and could lead to complete blackouts as well as damages to the system equipment. In order to solve this challenge, this study proposes a new coordinated optimal load frequency control plus modified control signal to superconducting magnetic energy storage for compensating the microgrid frequency deviation (∆ f ). To prove the effectiveness of the proposed coordinated control strategy, an islanded microgrid was tested for the MATLAB/Simulink simulation. The physical constraints of the turbines such as generation rate constraints and speed governor dead band are considered in this study. The results confirmed the effectiveness and robustness of the proposed coordination performance against all scenarios of different load profiles, wind power fluctuation, and system uncertainties in microgrid integrated with high penetration of wind farms. Moreover, the results have been compared with both: the optimal load frequency control with/without the effect of conventional superconducting magnetic energy storage.